Blockade of Discoidin Domain Receptor 2 as a Strategy for Reducing Inflammation and Joint Destruction in Rheumatoid Arthritis Via Altered Interleukin‐15 and Dkk‐1 Signaling in Fibroblast‐Like Synoviocytes. Issue 6 (2nd May 2020) - Mu, Nan; Gu, Jin‐Tao; Huang, Tong‐Lie; Liu, Nan‐Nan; Chen, Hui; Bu, Xin; Zheng, Zhao‐Hui; Jia, Bo; Liu, Jun; Wang, Bao‐Long; Wang, Ying‐Mei; Zhu, Zhen‐Feng; et al.
Abstract : Objective: This study was undertaken to uncover the pathophysiologic role of discoidin domain receptor 2 (DDR‐2), a putative fibrillar collagen receptor, in inflammation promotion and joint destruction in rheumatoid arthritis (RA). Methods: In synovial tissue from patients with RA and from mice with collagen antibody–induced arthritis (CAIA) (using Ddr2 −/− and DBA/1 mice), gene and protein expression levels of DDR‐2, interleukin‐15 (IL‐15), and Dkk‐1 were measured by quantitative reverse transcription–polymerase chain reaction, Western blotting, and immunohistochemistry. Gene knockdown of DDR2 in human RA fibroblast‐like synoviocytes (FLS) was conducted via small interfering RNA. Interaction between the long noncoding RNA H19 and microRNA 103a (miR‐103a) was assessed in RA FLS using RNA pulldown assays. Cellular localization of H19 was examined using fluorescence in situ hybridization assays. Chromatin immunoprecipitation and dual luciferase reporter assays were applied to verify H19 transcriptional and posttranscriptional regulation by miR‐103a. Results: DDR2 messenger RNA (mRNA) expression was significantly associated with the levels of IL‐15 and Dkk‐1 mRNA in the synovial tissue of RA patients (r 2 = 0.2022–0.3293, all P < 0.05; n = 33) and with the serum levels of IL‐15 and Dkk‐1 in mice with CAIA ( P < 0.05). In human RA FLS, activated DDR‐2 induced the expression of H19 through c‐Myc. Moreover, H19 directly interacted with and promoted the degradation of miR‐103a. Conclusion: These results indicate a novel role for activated DDR‐2 in RA FLS, showing that DDR‐2 is responsible for regulating the expression of IL‐15 and Dkk‐1 in RA FLS and is involved in the promotion of inflammation and joint destruction during pathophysiologic development of RA. Moreover, DDR‐2 inhibition, acting through the H19–miR‐103a axis, leads to reductions in the inflammatory reaction and severity of joint destruction in mice with CAIA, suggesting that inhibition of DDR‐2 may be a potential therapeutic strategy for RA.